The markets for force : privatization of security across world regions - Petersohn, Ulrich; Dunigan, Molly (EBL-Schweitzer, 2015)
The Markets for Force compares the markets for private military and security services across the globe, examining how local markets evolve and interact with regional politics and geostrategic context.